2022
DOI: 10.2196/preprints.37665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patients’ willingness to provide their clinical data for research purposes and acceptance of different consent models: Findings from a representative survey of cancer patients in Germany (Preprint)

Abstract: BACKGROUND Secondary use of clinical data for biomedical research purposes holds great potential for various types of non-interventional, data-driven studies. Patients’ willingness to support research with their clinical data is a crucial prerequisite for research progress. OBJECTIVE The aim of the study is to learn about patients’ attitudes and expectations regarding secondary use of their cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Our study further found a majority of physicians viewing the support of secondary use as a moral duty of peer physicians (68%). This view resonates with the results of a study we have previously conducted in which cancer patients attributed an obligation to their physicians to support secondary use (91%) (12). An ethical discussion of such a duty to support secondary use seems essential in order to resolve the tension of conflicting duties.…”
Section: Discussionsupporting
confidence: 86%
“…Our study further found a majority of physicians viewing the support of secondary use as a moral duty of peer physicians (68%). This view resonates with the results of a study we have previously conducted in which cancer patients attributed an obligation to their physicians to support secondary use (91%) (12). An ethical discussion of such a duty to support secondary use seems essential in order to resolve the tension of conflicting duties.…”
Section: Discussionsupporting
confidence: 86%